How do gynecologists face to social problems among women cancer survivors?. Issue 5 (24th March 2021) - Endo, Motoki
Abstract: In recent decades, surgical techniques, new anticancer drugs' development, and radiation equipment have led to continuous improvements in cancer survival rates and quality of life of cancer survivors (CSs). While 61.0% of gynecological cancer survivors (GCS) in Japan belonged to a working‐age group (20–64 years old), the number of working GCS within the working‐age population has increased. In Japan, it seems that there has been more interest in striking a balance between cancer treatment and work, especially since 2016 when the Cancer Control Act was amended and national guidelines for working CSs were published. Maintaining employment after gynecological cancer diagnosis remains an important issue for not only GCS and their families but also employers and society. GCS suffered from various symptoms including cancer‐related fatigue, pain, menopausal symptoms, lymphedema, and psychological distress, which made maintaining employment difficult for them. Full return to work (RTW) rate at 365 days after the initial days of sick leave among was 77.6% and median time to full RTW among GCSs was 172 days. Five‐year work continuance rate after RTW among GCSs was 63.4%. It is better for gynecologists to write a certificate for workplace in words of not "symptoms, " but "caseness words (such as, workable as long as it is sedentary or clerical work. Partial RTW (4‐h work, 6‐h work) might be desirable for a while after RTW, " in order to support GCSs' maintaining employment.